Observational study of long-term persistent elevation of neurodegeneration markers after cardiac surgery - DiMeglio, Matthew (Sci Rep, 2019)
Surgery and anesthesia induce inflammatory changes in the central nervous system, which ultimately lead to neuronal damage concomitant with an increase in the level of neurodegeneration markers. Despite some experimental data showing prolonged activation of the immune system post-surgery, no study has determined the extent of long-term elevation of neurodegeneration markers. The purpose of this study was to investigate the serum levels of tau protein, ubiquitin carboxyl-terminal hydrolase L1 (UCH-L1), neurofilament light (NF-L), and glial fibrillary acidic protein (GFAP) after elective cardiac surgery with the implementation of cardiopulmonary bypass (CPB). The serum levels of these markers from 30 patients were compared longitudinally to the baseline (pre-surgery or t(0)), at 24 hours (t(+24)), at 7 days (t(+7d)), and at 3 months (t(+3m)). The secondary outcome was the production of macrophage-colony stimulating factor (M-CSF) and tumor necrosis factor-α (TNF-α) in vitro by isolated monocytes in response to lipopolysaccharide (LPS) as the measure of immune system activation. The tertiary outcome was the serum level of C-reactive protein (CRP), serum amyloid P (SAP), and α-2-macroglobulin (A2M). Serum levels of tau protein increased 24 hours after surgery (p = 0.0015) and remained elevated at 7 days (p = 0.0017) and three months (p = 0.036). Serum levels of UCH-L1 peaked at 24 hours (p = 0.00055) and normalized at 3 months. In vitro secretion of M-CSF by LPS-stimulated peripheral monocytes, but not TNFα, correlated highly (r = 0.58; p = 0.04) with persistent elevation of serum tau levels at 3 months. The serum CRP and SAP increases correlated with tau post-CPB levels significantly at 3 months. We demonstrated that elevation of serum tau levels at 24 hours, 7 days, and 3 months after heart surgery is concomitant with some traits of inflammation after CPB. The elevation of tau several weeks into recovery is significantly longer than expected.